Предмет: Алгебра,
автор: Нюта1000
решить систему неравенств:
Ответы
Автор ответа:
0
{3^(2x - 3) - 29*3^(x - 3) + 2 <= 0
{(x^2 - x + 2) / (x^2 - x) + (5x - 10) /(x - 4) <= (6x - 2) / x
Сначала упростим каждое нер--во отдельно.
3^2x/ 3^3 - 29*3^x/ 3^3 + 2 <= 0
3^2x - 29*3^x + 54 <= 0
D = b^2 - 4ac = (-29)^2 - 4*3*54 = 841 - 648 = 193 > 0
Похожие вопросы
Предмет: Информатика,
автор: johnhewasanimposter
Предмет: Геометрия,
автор: kata67109
Предмет: Английский язык,
автор: Voloduki
Предмет: Физика,
автор: mart89